2016
DOI: 10.1016/j.trci.2016.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Profiling the dynamics of CSF and plasma Aβ reduction after treatment with JNJ‐54861911, a potent oral BACE inhibitor

Abstract: ObjectivesSafety, tolerability, pharmacokinetics, and pharmacodynamics of a novel β-site amyloid precursor protein cleaving enzyme 1 (BACE1) inhibitor, JNJ-54861911, were assessed after single and multiple dosing in healthy participants.MethodsTwo randomized, placebo-controlled, double-blind studies were performed using single and multiple ascending JNJ-54861911 doses (up to 14 days) in young and elderly healthy participants. Regular blood samples and frequent CSF samples, up to 36 hours after last dose, were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
53
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(59 citation statements)
references
References 29 publications
6
53
0
Order By: Relevance
“…Subsequent intramembrane proteolysis catalyzed by the c-secretase complex releases amyloid-b peptides of 38-43 amino acids, which form the pathogenic oligomeric and fibrillary Ab species (Haass, 2004;Masters & Selkoe, 2012). Inhibition of BACE-1 by low-molecular-weight compounds has emerged as a new concept for treatment of AD (Vassar et al, 2014;Eketjall et al, 2016;Kennedy et al, 2016;Timmers et al, 2016Timmers et al, , 2017Yan et al, 2016;Cebers et al, 2017) by preventing the generation and deposition of Ab rather than just treating the dementia symptoms. However, limited selectivity for BACE-1 over cathepsin D (CatD), the off-target inhibition of which is a principal driver of ocular toxicity, and liver enzyme elevation have led to the termination of some early BACE-1 inhibitors in clinical trials (May et al, 2011(May et al, , 2015Zuhl et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent intramembrane proteolysis catalyzed by the c-secretase complex releases amyloid-b peptides of 38-43 amino acids, which form the pathogenic oligomeric and fibrillary Ab species (Haass, 2004;Masters & Selkoe, 2012). Inhibition of BACE-1 by low-molecular-weight compounds has emerged as a new concept for treatment of AD (Vassar et al, 2014;Eketjall et al, 2016;Kennedy et al, 2016;Timmers et al, 2016Timmers et al, , 2017Yan et al, 2016;Cebers et al, 2017) by preventing the generation and deposition of Ab rather than just treating the dementia symptoms. However, limited selectivity for BACE-1 over cathepsin D (CatD), the off-target inhibition of which is a principal driver of ocular toxicity, and liver enzyme elevation have led to the termination of some early BACE-1 inhibitors in clinical trials (May et al, 2011(May et al, , 2015Zuhl et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Seven days of dosing with the supratherapeutic dose, 150 mg, resulted in a mean JNJ-54861911 plasma C max of 1380 ng/mL, which is substantially above maximal therapeutic levels (C max at 50 mg equals 364 ng/mL). 5 Expectedly, ER analysis of these data demonstrated a positive and statistically significant slope of 0.0133 milliseconds per ng/mL. However, in the expected therapeutic dose range (up to 25 mg of JNJ-54861911), the extent of QT prolongation is expected to be consistently smaller than 5 milliseconds, that is, a mean of -0.4 milliseconds (90%CI, -0.8 to 0.1 milliseconds) at a 25mg dose (geometric mean C max , 71 ng/mL, based on population PK modeling).…”
Section: Discussionmentioning
confidence: 99%
“…Both studies have been described in detail elsewhere. 5 Both studies were double-blind, randomized, and placebocontrolled. All subjects were required to have a normal baseline ECG with QTc interval <430 milliseconds for men and <450 milliseconds for women in the SAD study, and <450 milliseconds for men and <470 milliseconds for women in the MAD study.…”
Section: Sad and Mad Studiesmentioning
confidence: 99%
“…Human studies have shown similar results concerning the reduction of Aβ levels in response to treatment with BACE-1 inhibitor atabecestat. Results of a placebo-controlled phase I study in patients with early AD showed an up to 95% reduction of toxic Aβ levels in the CSF upon treatment with atabecestat [58]. With these promising results of reduced Aβ levels, severe ascription to the Aβ hypothesis would logically conclude parallel reductions in cognitive impairment.…”
Section: Nftmentioning
confidence: 99%
“…Drug candidates developed in this scheme include inhibitors of BACE-1 and γ-secretase. Evidence as to the pharmacologic engagement of BACE-1 inhibitors is often inferred from a reduction in Aβ concentrations subsequent to treatment with such an inhibitor, as determined by amyloid positron-emission tomography (amyloid PET) or immunoassay analysis [57,58]. A 2017 study conducted by Villarreal et al, using a murine model of advanced age, showed reduction of plasma Aβ 1-40 by 98% and Aβ 1-42 by 90% upon treatment with BACE-1 inhibitor verubecestat.…”
Section: Nftmentioning
confidence: 99%